Detection and Characterization of Autoagglutination Activity by Campylobacter jejuni - Misawa, Naoaki (American Society for Microbiology (ASM), 2000)
In several gram-negative bacterial pathogens, autoagglutination (AAG) activity is a marker for interaction with host cells and virulence. Campylobacter jejuni strains also show AAG, but this property varies considerably among strains. To examine the characteristics of C. jejuni AAG, we developed a quantitative in vitro assay. For strain 81-176, which shows high AAG, activity was optimal for cells grown for ≤24 h, was independent of growth temperature, and was best measured for cells suspended in phosphate-buffered saline at 25°C for 24 h. AAG activity was heat labile and was abolished by pronase or acid-glycine (pH 2.2) treatment but not by lipase, DNase, or sodium metaperiodate. Strain 4182 has low AAG activity, but extraction with water increased AAG, suggesting the loss of an inhibitor. Strain 6960 has weak AAG with no effect due to water extraction. Our study with clinical isolates suggests that C. jejuni strains may be grouped into three AAG phenotypes. A variant derived from strain 81116 that is flagellate but immotile showed the strong AAG exhibited by the parent strain, suggesting that motility per se is not necessary for the AAG activity. AAG correlated with both bacterial hydrophobicity and adherence to INT407 cells. Mutants which lack flagella (flaA, flaB, and flbA) or common cell surface antigen (peb1A) were constructed in strain 81-176 by natural transformation-mediated allelic exchange. Both AAG activity and bacterial hydrophobicity were abolished in the aflagellate mutants but not the peb1A mutant. In total, these findings indicate that C. jejuni AAG is highly associated with flagellar expression.